Physical and physiological determinants of motorcycling performance: a systematic review - Rodrigues, T.; Neiva, H.; Marques, D. (Strength and Conditioning Journal, 2025)
Competitive motorcycling is a physically demanding sport requiring high levels of strength, endurance, and neuromuscular control. However, research on optimizing training strategies and injury prevention remains limited. This systematic review analyzes the physical and physiological demands of motorcycling, aiming to provide insights for riders and coaches. A comprehensive search in PubMed, Web of Science, and Scopus identified 2,809 studies, with 17 meeting the inclusion criteria. Screening was performed using Rayyan, and study quality was assessed using the JBI tool for cross-sectional studies. Key findings indicate that riders frequently operate at 80-100% of maximum heart rate, emphasizing the importance of aerobic and anaerobic conditioning through running, cycling, and high-intensity interval training. Postrace lactate levels typically exceed 6 mmol/L, necessitating riders to engage in sprint-based and strength-based training. Grip strength and upper limb isometric endurance are critical, requiring targeted resistance exercises. In addition, effective recovery strategies such as active recovery, cryotherapy, and strategic nutrition help reduce fatigue and optimize performance. Research gaps persist in long-term physiological adaptations, training methodologies, and psychological influences. Future studies must identify evidence-based guidelines to improve motorcycling training and recovery protocols. This review highlights the importance of specialized conditioning programs tailored to motorcycling demands, thereby optimizing competitive performance.